Treat-to-target in rheumatoid arthritis: a real-world study of the application and impact of treat-to-target within the wider context of patient management, patient centricity and advanced therapy use in Europe - Bruno Fautrel; Rieke Alten; Yves Piette; Roberto Caporali; Susana Romero-Yuste; Jasper Broen; Katrien Van Beneden; Martin Welcker; Peter C. Taylor; Oliver Howell; Elke Rottier; Monia Zignani (RMD Open, 2022)
Background While treat-to-target (T2T) is endorsed for the management of rheumatoid arthritis (RA), data on the degree of implementation in clinical practice are limited. This study investigated the use of T2T for RA in a real-world setting across Europe.Methods The Adelphi RA Disease-Specific Programme was a point-in-time survey of rheumatologists and their consulting patients with RA conducted between January and October 2020 in Belgium, France, Germany, Italy, Spain and the UK. Rheumatologists completed an attitudinal survey, and a record form for their next 10–12 consulting patients, who were invited to voluntarily complete a patient-reported questionnaire. Data collected included clinical characteristics, treatment patterns and attitudes towards T2T.Results Overall, 316 rheumatologists provided data for 3120 patients, of whom 1108 completed the questionnaire. While 86.1% of rheumatologists estimated using T2T principles in clinical practice, only 66.6% of patients were reported by their physician to be managed using a T2T approach. Achieving disease remission was the most commonly reported treatment goal identified by rheumatologists (79.7%), followed by symptom control (47.8%) and reducing impact on quality of life (44.5%). 40.8% of rheumatologists and their patients were in agreement that a treatment goal had been set. When there was agreement on treatment goals, we observed better patient satisfaction, engagement and treatment success.Conclusions Despite recommendations, the T2T approach in RA appears to be suboptimally implemented in clinical practice. This highlights the importance of patient-centricity in the decision-making process to define meaningful targets and select appropriate treatments to improve disease outcomes.